Properties of cement mortar in substitution with waste fine glass powder and environmental impact study. (January 2020) - Patel, Dhirendra; Shrivastava, R.; Tiwari, R.P.; Yadav, R.K.
Abstract: The mutual relationship between nature's and human's creation is depriving because of quenching of earth's resources drastically to fulfil the demand of world's population. Now to synchronize the alarming signals of unbalancing health of nature, the researchers are tuning up with ecological development. One of the basic solutions to create the balance between them; is by using waste material in the construction and building industry looking for reusing material of such a nature. The glass powder has properties deemed to be incorporated in making mortar and concrete as substitution of cement. Meanwhile, to make this substitution sound relevant to designated as competent in the category of pozzolana material, numerous work is going on. In a present study we analyze 45-μm glass powder at 0–20% substitution to describe its essence in the response of fresh, short- and long-term properties of blended mortar mix and the durability concern. The results signify that SAI value lies between 90 and 126%, and lime reactivity is close to fly ash based lime mortar. Moreover, the compressive and transverse strength at the later stage showing higher strength than control and from durability side the results are within the safe limit. Apart from that, the authentication of the results is also carried out by Combined SEM & EDX images of the paste and mortar. The results of an environmental impact study of the control and blended paste signifying 20% reduction in indexes of the sustainable environment for glass powder mix at 20% as compared to control. Highlights: Critical analysis of two closely particle sizes 63μ to 45μ. Ecological balanced material. 20% reduction in indexes of the sustainable environment. Improvement in engineering properties of blended glass powder mix with validation through SEM&EDX.